2015
DOI: 10.1039/c5ra13088c
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal complex redox shuttles for dye-sensitized solar cells

Abstract: An important link exists between the selected molecular structure of a sensitizer and the employed shuttle electrolyte to achieve high conversion efficiency in dye-sensitized solar cells (DSSCs). So far, the most commonly used redox mediator is iodide/triiodide (I − /I 3 − ), which has shown advantages such as desirable kinetic properties and high carrier collection efficiencies. However, it has several disadvantages including a low redox potential, corrosion toward metal materials and competitive blue light a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 130 publications
0
49
0
Order By: Relevance
“…The M 0 species produced by reduction of M + at the CE back diffuses to the PE M 0 (CE) → M 0 (PE) (28) in order to participate to the oxidized dye regeneration process. The excited dye can either inject an electron into the semiconductor oxide conduction band or be deactivated to the initial dye form together with the emission of light (fluorescence) or heat: D 0 * hν or heat → D 0 (29) For efficient DSSC operation the latter process should be much slower than electron injection.…”
Section: Reduced Mediator Transport From Counter Electrode To Photoelmentioning
confidence: 99%
“…The M 0 species produced by reduction of M + at the CE back diffuses to the PE M 0 (CE) → M 0 (PE) (28) in order to participate to the oxidized dye regeneration process. The excited dye can either inject an electron into the semiconductor oxide conduction band or be deactivated to the initial dye form together with the emission of light (fluorescence) or heat: D 0 * hν or heat → D 0 (29) For efficient DSSC operation the latter process should be much slower than electron injection.…”
Section: Reduced Mediator Transport From Counter Electrode To Photoelmentioning
confidence: 99%
“…DSCs have been shown to reach power conversion efficiencies (PCEs) of >14 % under 1 sun conditions and >28 % in low light, making them a cost‐effective alternative to current renewable energy sources . The tunable nature of the sensitizers in dye‐sensitized renewable energy areas, including photochemical cells, solar batteries, and DSCs, has created a large push in research efforts for sensitizer design . The prevalent donor–π bridge–acceptor (D–π–A) structure is common to all dye‐sensitized applications, as it is amenable to flexible synthetic approaches that enable the tailoring of absorption profiles.…”
Section: Figurementioning
confidence: 99%
“…Several synthetic approaches based on organic (Sauvage, 2014), inorganic (Bergeron et al, 2005;Burschka et al, 2012;Carli et al, 2013), or organometallic compounds (Carli et al, 2016;Spokoyny et al, 2010;Sun et al, 2015;Magni et al, 2016) have been reported with [Co(bpy) 3 ] 2+/3+ and [Co(phen) 3 ] 2+/3+ (where bpy = 2,2 0 -bipyridine and phen = 1,10-phenanthroline) as redox couples. Notably, DSSCs using cobalt redox pairs mostly tether to pyridine-type ligands with complex formal charge (2+/3+) (Ben Aribia et al, 2013;Lee et al, 2015;Bella et al, 2016;Kashif et al, 2013;Pashaei et al, 2015;Giribabu et al, 2015), displaying few structural deviations mainly by varying the ligand backbone with groups of different donating/withdrawing data reports ability (Pashaei et al, 2015;Xu et al, 2013), and without nonneutral ligands in the coordination sphere.…”
Section: Structure Descriptionmentioning
confidence: 99%